HARVESTING TIME AND VIABILITY OF Ixora coccinea 'DWARF RED COCCINEA' POLLEN - David Leung (SEAMEO BIOTROP, 2021)
The cultivated variety of the non-native I. coccinea, cv. ‘Dwarf Red Coccinea’ (DRC), is the most popular and widely distributed throughout Thailand. However, knowledge regarding its pollen morphology and fertility for plant breeding purposes remains limited. This study aimed to investigate the quantity, viability, and germinability of pollen grains collected from the flowers of DRC at different times during a summer day, specifically from 8 AM to 4 PM. Pollen quantity was determined using a haemacytometer, while pollen viability and germinability were examined after staining with 1% acetocarmine and germinating the pollen on a modified agar-gelled germination medium, respectively. Pollen collected at 10 AM exhibited the highest pollen density (53.3 × 10⁴ pollen mL⁻¹) and viability percentage (72.05%). When these pollen grains were germinated on an artificial medium supplemented with various sucrose concentrations, the highest in vitro pollen germinability was observed on a medium containing 10% sucrose. Therefore, the optimal time to collect I. coccinea, cv. ‘Dwarf Red Coccinea’ pollen is at 10 AM. Nevertheless, further investigations are recommended to examine the effects of daily or hourly environmental variations, particularly ambient temperature and humidity, on the quantity and quality of harvestable pollen, as well as on pistil phenology, in order to develop a more comprehensive breeding strategy for Ixora species.